Fast weight recovery, metabolic rate adjustment and gene-expression regulation define responses of cold-stressed honey bee brood. (January 2021) - Ramirez, Leonor; Luna, Facundo; Mucci, Claudio Andoni; Lamattina, Lorenzo
Highlights: Identification of metabolic adjustments in cold-stressed honey bee brood. After cold-stress, compensatory mechanisms support 24 h of fast growth rate recovery. Higher metabolic rate and expression of MUP2 occurs in cold-stressed brood. IIS and AKH pathways synchronize growth metabolism and cold-stress responses. Abstract: In temperate climates, low ambient temperatures in late winter and in spring can result in cold stress conditions in brood areas of weakened honey bee colonies, leading to increased levels of developmental interruptions and death of the brood. Very little is known about the physiological and molecular mechanisms that regulate honey bee brood responses to acute cold-stress. Here, we hypothesized that central regulatory pathways mediated by insulin/insulin-like peptide signalling (IIS) and adipokinetic hormone (AKH) are linked to metabolic changes in cold-stressed honey bee brood. A. mellifera brood reared at suboptimal temperatures showed diminished growth rate and arrested development progress. Notably, cold-stressed brood rapidly recovers the growth in the first 24 h after returning at control rearing temperature, sustained by the induction of compensatory mechanisms. We determined fast changes in the expression of components of IIS and AKH pathways in cold-stressed brood supporting their participation in metabolic events, growth and stress responses. We also showed that metabolic rate keeps high in brood exposed to stress suggesting a role in energy supply for growth and cell repair. Additionally, transcript levels of the uncoupling protein MUP2 were elevated in cold-stressed brood, which could indicate that this protein acts in the heat generation through mitochondrial decoupling mechanisms and/or in the ROS attenuation. Physiological, metabolic and molecular mechanisms that shape the responses to cold-stress in honey bee brood are addressed and discussed.